Do magnocellular and parvocellular ganglion cells avoid short-wavelength cone input? - Sun, H; Smithson, H; Zaidi, Q; Lee, B (2006)
We recently developed a new technique to measure cone inputs to visual neurons and used this technique to seek short-wavelength-sensitive (S) cone inputs to parasol, magnocellular (MC) and midget, parvocellular (PC) ganglion cells. Here, we compare our physiological measurements of S-cone weights to those predicted by a random wiring model that assumes cells' receptive fields receive input from mixed cone types. The random wiring model predicts the average weights of S-cone input to be similar to the total percentage of S-cones but with considerable scatter, and the S-cone input polarity to be consistent with that of PC cells' surround and of MC cells' center. This is not consistent with our physiological measurements. We suggest that the ganglion cells' receptive fields may have a mechanism to avoid S-cone inputs, as is the case in the H1 horizontal cells. Previous reports of S-cone inputs, in particular substantial input to MC cells, are likely to reflect variation in prereceptoral filtering and/or the failure to correct for variation in macular pigment.